2017
DOI: 10.1038/s41598-017-00813-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of multimodal analgesic techniques for preventing chronic postsurgery pain under different surgical categories: a meta-analysis

Abstract: The purpose of this meta-analysis was to compare the efficacy and safety of regional anesthesia to manage chronic postsurgery pain. A systematic search of PubMed, EmBase, and the Cochrane Central Register of Controlled Trials was performed to identify randomized controlled trials that focused on chronic pain frequency, analgesic consumption, and adverse effects under different surgical categories. We collected 21 trials assessing 1,980 patients for our meta-analysis. The summary of relative risks (RRs) and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…Nationwide research in the United States of America showed tremendous variations in the utilization of multimodal therapy use not accounted for by patient or hospital characteristics and the mean probability of receiving multimodal analgesia as 90.4%. However, the presence of this practice in different hospitals of Ethiopia is not known yet making it difficult to compare the results of this research [9][10][11][12].…”
Section: Discussionmentioning
confidence: 98%
“…Nationwide research in the United States of America showed tremendous variations in the utilization of multimodal therapy use not accounted for by patient or hospital characteristics and the mean probability of receiving multimodal analgesia as 90.4%. However, the presence of this practice in different hospitals of Ethiopia is not known yet making it difficult to compare the results of this research [9][10][11][12].…”
Section: Discussionmentioning
confidence: 98%
“…Example of asymmetrical and symmetrical funnel plots with author commentary. Funnel plots were generated by extracting data from Zhou et al 91 and Zenebe et al 92 The funnel plot is a scatter plot that displays the effect estimates from individual studies against a measure of each study size. As detailed in the graph, the horizontal axis represents some measure of effect estimate, while the vertical axis represents some measure of study size.…”
Section: Authors Should Evaluate the Quality (Certainty) Of Evidence ...mentioning
confidence: 99%
“…Son utilisation chez ces patients repose sur le bon sens clinique. Une littérature de plus en plus abondante semble confirmer que les techniques d'analgésie locorégionale préviendraient le développement des douleurs chroniques postopératoires [26]. Enfin, dans les populations «opioïdes dépendantes», le bénéfice de la kétamine a été évalué dans trois essais randomisés dans différents types de chirurgie (orthopédique, chirurgie du rachis et lithotripsie) [27][28][29] et son utilisation semble apporter un bénéfice important.…”
Section: Point 4 : Consultation Spécialisée En Douleur Chroniqueunclassified